Preparation method and application of medical carbon fiber prepreg tape
By forming a three-dimensional network hydrogel structure on carbon fibers, the interfacial interaction between carbon fibers and polyaryletherketones is enhanced, solving the problem of poor wettability between carbon fibers and polyaryletherketones. This results in a carbon fiber medical prepreg tape with high biosafety and excellent mechanical properties, suitable for biomedical materials.
Patent Information
- Application Number
- CN202411617752.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-07
AI Technical Summary
Existing technologies are insufficient to effectively improve the wettability between carbon fibers and polyaryletherketones, resulting in weak interfacial interactions, which affect the mechanical properties of the composite material and pose a risk of cytotoxicity, making it difficult to meet the requirements of biomedical materials.
A three-dimensional network hydrogel structure is formed by a vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer and a multi-arm polyethylene glycol derivative with active functional groups at the end of the copolymer via Michael addition reaction, which fixes polyarylether ketone on carbon fibers and enhances interfacial interaction.
It achieves high biocompatibility and excellent mechanical properties in carbon fiber medical prepreg tape, with a shear strength of over 70.0 MPa and no cytotoxic side effects, making it suitable for biomedical materials.
Smart Images

Figure CN119264490A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical composite materials, and in particular relates to a preparation method and application of a carbon fiber medical prepreg tape. Background Art
[0002] Orthopedic implant medical devices such as intramedullary nails, bone nails and bone plates made of continuous carbon fiber reinforced polyaryletherketone materials have achieved remarkable results in clinical applications. Such medical device products are generally prepared by molding carbon fiber / polyaryletherketone unidirectional prepreg. The key point of preparing carbon fiber / polyaryletherketone prepreg for such medical products is that it needs to have excellent biosafety.
[0003] Carbon fiber has a six-membered ring stable structure and few surface active groups; polyaryletherketone has fast crystallization, high melt viscosity and processing temperature, and the two have poor mutual wettability. Polyaryletherketone is usually difficult to completely infiltrate the carbon fiber tow, and cannot bring out the excellent performance of carbon fiber as a reinforcement, resulting in weak interfacial interaction. As a result, in the actual processing and molding of composite materials, the two cannot be well combined together, affecting their mechanical properties.
[0004] As a kind of special polymer material, polyaryletherketone includes polyetheretherketone, polyetherketoneketone, polyetherketone, polyetheretherketoneketone or polyetherketoneetherketoneketone, etc. The reported preparation method of continuous carbon fiber reinforced polyaryletherketone unidirectional prepreg is as follows:
[0005] CN114559685A discloses a carbon fiber-polyaryletherketone composite unidirectional prepreg tape and a preparation method thereof, wherein an amphiphilic polyoxyethylene derivative is first used to size the carbon fiber, and the carbon fiber tow is expanded at a certain lower temperature, and then the sizing agent is removed, and then hot-melt composite with polyaryletherketone. The method has the advantages of using a sizing agent with excellent biocompatibility to size the carbon fiber, and subsequently removing the sizing agent, so that the composite material component is easier to meet the performance requirements for biomedical materials. However, because the sizing agent is removed, the "bridge" connecting the carbon fiber and the polyaryletherketone is removed, although in order to further increase the interface interaction between the carbon fiber and the polyaryletherketone, the patent further irradiates and remelts the polyaryletherketone reinforced with carbon fiber, however, it is still difficult to effectively avoid the problem of weak interface bonding force in the hot-melt composite process of carbon fiber and polyaryletherketone, and there is a potential risk that the carbon fiber is easy to slip and precipitate in the polyaryletherketone matrix during the subsequent application process.
[0006] CN114456539A discloses a method for preparing a high-solid content polyetheretherketone (PEEK) aqueous suspension and a composite fiber, the suspension comprising a dispersed phase PEEK resin powder and a surfactant and a continuous phase deionized water, with a solid content of 10-40% (mass); the composite fiber comprises a carbon fiber reinforced PEEK composite fiber, and the preparation method comprises: the surfactant is uniformly dispersed in deionized water, and the pH value of the solution is adjusted to 2-12 with an acid solution or an alkaline solution, the mixed solution is mixed dropwise with the PEEK resin powder to form a suspension, and then the suspension is coated on the surface of the carbon fiber, and after drying, it is kept at a constant temperature in a heat setting device and cooled to obtain. The polyetheretherketone of this method has the risk of falling off. In addition, industrial organic solvents such as acids and alkalis are used, which are polluting to the environment and difficult to remove, and have potential cytotoxicity risks, which are not conducive to use in biomedical materials.
[0007] CN114131785A discloses a method for preparing a high temperature resistant thermoplastic composite unidirectional prepreg tape, firstly preparing a resin solution, then after the fiber is fully infiltrated with the resin solution, performing a precipitation treatment, using a precipitating agent to precipitate the resin from the solution and attach it to the fiber, realizing solvent recovery and preliminary shaping of the prepreg tape, and then drying, high temperature shaping, cooling and winding to obtain a fiber reinforced high temperature resistant thermoplastic composite unidirectional prepreg tape. This patent uses highly toxic organic solvents such as N,N-dimethylformamide, which pollute the environment and are difficult to remove. It has a potential risk of cytotoxicity and is not conducive to use in biomedical materials.
[0008] CN116751381A discloses a method for preparing a high-performance carbon fiber reinforced polyetheretherketone (PEEK) prepreg and a PEEK-based plate, comprising the following steps: first, preparing a suspension containing PEEK; second, unfolding the carbon fiber tow and performing surface treatment to obtain pretreated carbon fiber; third, immersing the pretreated carbon fiber in the suspension for impregnation treatment, extruding after drying, and rolling up after cooling to obtain a carbon fiber reinforced polyetheretherketone prepreg. The suspension described in the patent contains multiple components such as polyvinyl alcohol, sodium dodecyl sulfate, multi-walled carbon nanotubes, polytetrafluoroethylene, aluminum oxide, PEEK, etc. Too many components make it difficult to ensure that a sufficiently high content of PEEK is fixed on the carbon fiber, and in terms of being used to make PEEK biomedical materials, it is difficult to ensure that there are no cytotoxic side effects due to the mixed components.
[0009] In view of this, improving the wettability between polyaryletherketone and carbon fiber and obtaining carbon fiber medical prepreg tapes that meet high biosafety and excellent mechanical properties remains a technical difficulty in the industry. Summary of the invention
[0010] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing and applying a carbon fiber medical prepreg tape. The carbon fiber medical prepreg tape prepared by the method of the present invention has no cytotoxic side effects, has excellent mechanical properties, can be used in vivo, and is suitable for preparing medical devices.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a method for preparing a carbon fiber medical prepreg tape, comprising: coating continuous carbon fibers in a polyaryletherketone suspension A and a polyaryletherketone suspension B; then pre-forming, drying, and shaping to obtain the carbon fiber medical prepreg tape;
[0013] The components of the polyaryletherketone suspension A include polyaryletherketone powder and a triblock copolymer; the components of the polyaryletherketone suspension B include polyaryletherketone powder and a multi-arm polyethylene glycol derivative terminated with active functional groups;
[0014] The triblock copolymer has a critical temperature, below which the aqueous solution of the triblock copolymer is in a mixed solution state; above which the aqueous solution of the triblock copolymer is in a gel state;
[0015] The specific process of coating the polyaryletherketone suspension A is as follows: at temperature a, immersing the continuous carbon fiber in the polyaryletherketone suspension A, and maintaining the continuous carbon fiber in the suspension A for a residence time t1; then raising the temperature of the polyaryletherketone suspension A system to temperature b, and maintaining the residence time t2; in this process, the temperature of the triblock copolymer solution in the suspension A is raised from the temperature a to the temperature b, wherein the value of a is less than the temperature value of the critical temperature, and the value of the temperature b is greater than the temperature value of the critical temperature, so that the triblock copolymer forms a gel on the continuous carbon fiber, thereby causing the polyaryletherketone powder to adhere to the continuous carbon fiber;
[0016] The triblock copolymer is a polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer terminated with vinyl sulfone;
[0017] The specific process of coating in the polyaryletherketone suspension B is as follows: immersing the continuous carbon fiber coated in the polyaryletherketone suspension A into the polyaryletherketone suspension B; during the immersion in the polyaryletherketone suspension B, the triblock copolymer attached to the continuous carbon fiber undergoes a Michael addition reaction with the multi-arm polyethylene glycol derivative terminated with active functional groups to generate a three-dimensional network structure hydrogel, and the polyaryletherketone powder is further fixed on the continuous carbon fiber.
[0018] As a thermosensitive nonionic surfactant, the vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer serves as a "bridge" connecting the interface between carbon fiber and polyaryletherketone, thereby enhancing the wettability of carbon fiber and polyaryletherketone resin. By increasing the temperature, the vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer will change from a solution state to a gel state, which can promote the polyaryletherketone resin to adhere to the carbon fiber more evenly.
[0019] At the same time, the hydrogel with a three-dimensional mesh structure formed by the vinyl sulfone-terminated PEG-PPG-PEG and the multi-arm polyethylene glycol derivative further fixes the polyaryletherketone powder attached to the carbon fiber on the carbon fiber, thereby increasing the content of the polyaryletherketone resin in the carbon fiber. The shear strength of the carbon fiber reinforced polyaryletherketone composite material profile made of the carbon fiber medical prepreg tape can reach more than 70.0MPa, and osteoblast culture research has proved that the composite material profile made of the carbon fiber medical prepreg tape has no cell toxicity and side effects, and can be used for polyaryletherketone medical materials. The PEG-PPG-PEG triblock copolymer enhances the interface interaction between polyaryletherketone and carbon fiber, and the composite effect is good.
[0020] The polyaryletherketone powders in the polyaryletherketone suspension A and the polyaryletherketone suspension B independently include any one of polyetheretherketone, polyetherketoneketone, polyetherketone, polyetheretherketoneketone or polyetherketoneetherketoneketone, or a combination of at least two thereof.
[0021] Preferably, the vinyl sulfone terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer has a structure as shown in Formula 1:
[0022]
[0023] Where x is 1-100, y is 1-100, and z is 1-100;
[0024] For example, 1, 2, 5, 10, 15, 20, 30, 50, 80, 90, 100, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0025] In the present invention, in order to circumvent the problem of poor interfacial compatibility between polyaryletherketone and carbon fiber, PEG-PPG-PEG triblock amphiphilic copolymer is used as a polymer nonionic surfactant, and the interfacial compatibility between polyaryletherketone and carbon fiber is promoted by adjusting the hydrophilicity and hydrophobicity of PEG-PPG-PEG. The hydrophilicity and hydrophobicity of PEG-PPG-PEG depends on the ratio of hydrophilic segment (ethylene glycol, EO) / hydrophobic segment (propylene glycol, PO). The higher the ethylene glycol content, the better the performance of the water-in-oil stabilizer. Therefore, PEG-PPG-PEG triblock copolymer is used as a "bridge". PEG-PPG-PEG triblock amphiphilic copolymer is also a thermosensitive polymer, which is generally in a solution state below 35°C. When the temperature is increased above 40°C, a phase transition will occur to form a solid gel, so that polyaryletherketone powder is firmly attached to the continuous carbon fiber thread.
[0026] In order to further fix the two, it is necessary to further form a hydrogel with a three-dimensional network structure. This can be achieved by modifying the carbon-carbon double bond at the end of the PEG-PPG-PEG triblock copolymer: the hydrogel is obtained by Michael addition reaction between the carbon-carbon double bond and the amino or thiol group of the multi-arm polyethylene glycol derivative.
[0027] The amphiphilic polymers of PEG-PPG-PEG terminated with carbon-carbon double bonds include PEG-PPG-PEG terminated with vinyl sulfone and PEG-PPG-PEG terminated with acrylate. Experimental studies have shown that the advantages of PEG-PPG-PEG terminated with vinyl sulfone over PEG-PPG-PEG terminated with acrylate are extremely obvious in the present invention:
[0028] First, in terms of using the temperature sensitivity of the material to attach polyaryletherketone to continuous carbon fiber threads, the experiment found that the gel formed by acrylate-terminated PEG-PPG-PEG at elevated temperature easily caused the attached polyaryletherketone powder to fall off and not adhere firmly. This is because the ester bond structure of the acrylate in acrylate-terminated PEG-PPG-PEG is easily hydrolyzed, which causes the temperature sensitivity of acrylate-terminated PEG-PPG-PEG to be unable to be well utilized in attaching polyaryletherketone powder, resulting in failure of normal production. The vinyl sulfone structure of vinyl sulfone-terminated PEG-PPG-PEG is particularly stable, and the chemical bond is strong and not easy to break. When the temperature is raised, the vinyl sulfone-terminated PEG-PPG-PEG undergoes a liquid-solid phase transition from solution to gel, and the adhesion is strong and stable. The gel formed by the solution system containing the thermosensitive triblock copolymer can firmly attach the continuous carbon fiber thread to polyaryletherketone.
[0029] Secondly, in terms of further fixing polyaryletherketone on the three-dimensional network structure hydrogel, acrylate-terminated PEG-PPG-PEG not only causes the polyaryletherketone attached to the continuous carbon fiber thread to have weak adhesion, but also easily falls off, resulting in the inability to produce normally. This is also because the hydrogel adhesion formed by acrylate-terminated PEG-PPG-PEG is far less strong than that of vinyl sulfone-terminated, and the ester bond contained in acrylate-terminated PEG-PPG-PEG is particularly easy to degrade, and the three-dimensional network structure of the hydrogel is not easy to maintain for a long time. The degradation of the hydrogel formed by acrylate-terminated PEG-PPG-PEG will cause the polyaryletherketone fixed on the continuous carbon fiber thread to fall off, resulting in the inability to produce normally. After verification, the present invention finds that the hydrogel formed by the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer is not easy to degrade for a long time, and the polyaryletherketone can be fixed on the carbon fiber thread well and stably for a long time.
[0030] In addition, the vinyl sulfone-terminated PEG-PPG-PEG used is an amphiphilic polymer, the PEG segment structure is hydrophilic, and the PPG segment structure is hydrophobic. The hydrophilicity and hydrophobicity of the vinyl sulfone-terminated PEG-PPG-PEG can be adjusted by adjusting the ratio of the hydrophilic and hydrophobic structures of PEG-PPG-PEG, thereby promoting the interfacial compatibility between polyaryletherketone and carbon fiber.
[0031] Preferably, the preparation method of the vinyl sulfone terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer comprises:
[0032] The hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer, sodium hydride and divinyl sulfone are reacted to obtain the vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer.
[0033] Preferably, the hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer has a structure as shown in Formula 2:
[0034]
[0035] Where x is 1-100, y is 1-100, and z is 1-100;
[0036] For example, it can be 1, 2, 5, 10, 15, 20, 30, 50, 80, 90, 100, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values included in the said range.
[0037] The hydroxyl-terminated PEG-PPG-PEG triblock copolymers include various medical grade poloxamers, such as P124, P 188, P 338 or Any one or a combination of at least two of P 407.
[0038] Preferably, the hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer is mixed with sodium hydride in an anhydrous and oxygen-free solvent under nitrogen protection, and then divinyl sulfone is added to react.
[0039] The molar ratio of the hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to sodium hydride is (0.1-100):1; for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 50:1, 80:1, 90:1, 100:1, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0040] Preferably, the molar ratio of the hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to divinyl sulfone is (0.1-200):1, for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 20:1, 50:1, 80:1, 100:1, 180:1, 200:1, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0041] Preferably, the reaction temperature is 50-70°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, and specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0042] Preferably, the reaction time is 3-5 days, for example, 3 days, 4 days, 5 days, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Preferably, after the reaction, the PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone is obtained by filtering, rotary evaporation, extraction, drying, rotary evaporation and drying again.
[0044] Preferably, the multi-arm polyethylene glycol derivative terminated with active functional groups includes an amino-terminated multi-arm polyethylene glycol derivative and / or a thiol-terminated multi-arm polyethylene glycol derivative.
[0045] Preferably, the multi-arm polyethylene glycol derivative terminated with active functional groups includes any one of an amino-terminated three-arm polyethylene glycol derivative, an amino-terminated four-arm polyethylene glycol derivative, an amino-terminated six-arm polyethylene glycol derivative, an amino-terminated eight-arm polyethylene glycol derivative, a thiol-terminated three-arm polyethylene glycol derivative, a thiol-terminated four-arm polyethylene glycol derivative, a thiol-terminated six-arm polyethylene glycol derivative or a thiol-terminated eight-arm polyethylene glycol derivative, or a combination of at least two thereof.
[0046] The vinyl sulfone-terminated PEG-PPG-PEG used can be prepared by medical-grade PEG-PPG-PEG block copolymers, and the vinyl sulfone-terminated PEG-PPG-PEG and the multi-arm polyethylene glycol derivatives terminated with active functional groups have no cytotoxic side effects. The reaction system of the carbon fiber medical prepreg manufacturing process does not involve organic solvents, does not pollute the environment, and the prepared carbon fiber medical prepreg has no cytotoxic side effects and is suitable for use in biomedical materials.
[0047] Preferably, the preparation method of the polyaryletherketone suspension A comprises:
[0048] The polyaryletherketone powder, the polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer terminated with vinyl sulfone and water are mixed and stirred for the first time to obtain the polyaryletherketone suspension A.
[0049] Preferably, the mass ratio of the vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to the polyaryletherketone powder in the polyaryletherketone suspension A is (0.1-100):1; for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 50:1, 80:1, 90:1, 100:1, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0050] Preferably, the mass ratio of the vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer in the polyaryletherketone suspension A to the polyaryletherketone suspension A (the sum of the mass of the triblock copolymer, PEEK powder and water) is (0.01-0.5):1; for example, it can be 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.5:1, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0051] Preferably, the preparation method of the polyaryletherketone suspension B comprises:
[0052] The polyaryletherketone powder, the multi-arm polyethylene glycol derivative terminated with active functional groups and water are mixed and stirred to obtain the polyaryletherketone suspension B.
[0053] Preferably, the mass ratio of the multi-arm polyethylene glycol derivative terminated with active functional groups to the polyaryletherketone powder in the polyaryletherketone suspension B is (0.1-100):1; for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 50:1, 80:1, 90:1, 100:1, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0054] Preferably, the multi-arm polyethylene glycol derivative terminated with active functional groups comprises a structure as shown in any one of Formulas 3-6:
[0055]
[0056] Wherein n is 1-100, for example, it can be 1, 2, 5, 10, 15, 20, 30, 50, 80, 90, 100, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0057] Preferably, the number average molecular weight of the multi-arm polyethylene glycol derivative terminated with active functional groups is 200-50000, for example, it can be 200, 1000, 2000, 3000, 5000, 8000, 10000, 20000, 30000, 40000, 50000, and specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0058] The more arms of the multi-arm polyethylene glycol derivative terminated with active functional groups, the greater the molecular weight of polyethylene glycol, and the more the content and uniform distribution of polyaryletherketone in the polyethylene glycol network structure can be enhanced. In addition, the polyethylene glycol derivative is a multi-arm polyethylene glycol with terminal groups modified with active functional groups.
[0059] Preferably, the polyaryletherketone has a crystallinity greater than 5% and a melt index greater than 5 g / min.
[0060] Preferably, the thickness of the carbon fiber medical prepreg tape is 20-500μm, for example, it can be 20μm, 50μm, 80μm, 100μm, 200μm, 300μm, 400μm, 500μm, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Preferably, the carbon fiber substrate is formed by spinning carbon fiber yarns.
[0062] Preferably, the carbon fiber comprises carbon fiber tow.
[0063] The carbon fibers are continuous carbon fibers.
[0064] Preferably, the number of bundles of the carbon fiber bundle is 2-30K, for example, it can be 2K, 5K, 10K, 15K, 20K, 25K, 30K, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0065] Preferably, the single filament diameter of the carbon fiber bundle is 2-100um, for example, it can be 2μm, 5μm, 10μm, 20μm, 50μm, 80μm, 100μm, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] The particle size of the polyaryletherketone powder is 2-100um, for example, 2um, 10um, 20um, 50um, 100um, and specific values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0067] The specific process of coating in the polyaryletherketone suspension A is as follows: at a certain temperature a, the continuous carbon fiber is immersed in the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time t1. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature b, and then kept for a certain time t2.
[0068] Preferably, the temperature a is 10-30° C. For example, it can be 10° C., 15° C., 20° C., 30° C., and specific values between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific values included in the range.
[0069] Preferably, the residence time t1 is 10-18000s. For example, it can be 10s, 1000s, 5000s, 10000s, 15000s, 18000s, and specific values between the above values. Due to space limitations and for simplicity, the present invention will no longer exhaustively list the specific values included in the range.
[0070] Preferably, the temperature b is 35-75° C. For example, it can be 35° C., 45° C., 55° C., 65° C., and specific values between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific values included in the range.
[0071] Preferably, the residence time t2 is 10-18000s. For example, it can be 10s, 1000s, 5000s, 10000s, 15000s, 18000s, and specific values between the above values. Due to space limitations and for simplicity, the present invention will no longer exhaustively list the specific values included in the range.
[0072] Preferably, the critical temperature is 30-60° C. For example, it may be 30° C., 40° C., 50° C., 60° C., and specific values between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific values included in the range.
[0073] The prepreg tape after preforming is sequentially introduced into oven A, oven B, and oven C for drying to obtain a dried preformed tape, and the dried preformed tape is shaped to obtain the carbon fiber medical prepreg tape.
[0074] Preferably, the temperature of the oven A is 25-105°C, for example, 25°C, 30°C, 50°C, 60°C, and specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0075] Preferably, the residence time of the prepreg tape in oven A is 10-18000s, for example, it can be 10s, 1000s, 5000s, 10000s, 15000s, 18000s, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0076] Preferably, the temperature of the oven B is 25-180°C, for example, it can be 25°C, 30°C, 50°C, 80°C, 100°C, 130°C, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0077] Preferably, the residence time of the prepreg tape in the oven B is 10-18000s, for example, it can be 10s, 1000s, 5000s, 10000s, 15000s, 18000s, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0078] Preferably, the temperature of the oven C is 25-350°C, for example, it can be 25°C, 30°C, 50°C, 80°C, 100°C, 150°C, 200°C, 250°C, 300°C, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0079] Preferably, the residence time of the prepreg tape in the oven C is 10-36000s, for example, it can be 10s, 1000s, 5000s, 10000s, 15000s, 20000s, 30000s, 36000s, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0080] Preferably, cooling is further included after the shaping.
[0081] Preferably, the shaping temperature is 300-450°C, for example, it can be 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0082] Preferably, the shaping pressure is 0.5-10MPa, for example, it can be 0.5MPa, 1MPa, 2MPa, 5MPa, 8MPa, 10MPa, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0083] Preferably, the shaping time is 10-18000s, for example, it can be 10s, 1000s, 5000s, 10000s, 15000s, 18000s, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0084] Preferably, the preparation method specifically comprises:
[0085] S1. The carbon fiber is passed through a yarn spreading device to spread the yarn to obtain a carbon fiber substrate;
[0086] S2. The carbon fiber substrate obtained in S1 is introduced into a dipping tank containing a polyaryletherketone suspension A and a dipping tank containing a polyaryletherketone suspension B for coating to obtain a dipped carbon fiber;
[0087] S3. The impregnated carbon fiber obtained in S2 is introduced into a constant temperature bath for pre-forming to obtain a pre-formed tape;
[0088] S4. The predetermined tape obtained in S3 is sequentially introduced into oven A, oven B, and oven C for drying to obtain a dry predetermined tape;
[0089] S5. The dried pre-shaped tape obtained in S4 is introduced into a high-temperature pressure roller for shaping to obtain a shaped prepreg tape.
[0090] The yarn spreading temperature in step S1 is 20-200°C, for example, it can be 20°C, 50°C, 80°C, 100°C, 150°C, 200°C, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0091] The number of coatings in step S2 is 1-20 times, for example, 5 times, 6 times, 10 times, 15 times, 20 times, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0092] In a second aspect, the present invention provides a use of a carbon fiber medical prepreg tape prepared by the preparation method described in the first aspect in medical devices.
[0093] Preferably, the application includes application in 3D printing of medical materials, artificial prostheses, medical catheters, oral implants, maxillofacial bones, heart valves, infusion ports, pacemaker housings, medical aiming rods, medical aiming frames, human bone locking systems, medical wrenches, medical connectors, medical positioning frames, surgical head frames and retractor systems, medical handles, medical puncture needles, medical connectors, medical sutures, artificial bones, artificial joints, femoral condyles, bone nails, screws, anchors, rivets, intramedullary nails, bone plates, tibial trays, skull repair systems or spinal intervertebral fusion devices.
[0094] Compared with the prior art, the present invention has the following beneficial effects:
[0095] The invention provides a carbon fiber medical prepreg tape, wherein polyaryletherketone is attached and fixed on carbon fiber through a three-dimensional network hydrogel structure generated by Michael addition reaction of vinyl sulfone-terminated PEG-PPG-PEG and a multi-arm polyethylene glycol derivative terminated with an active functional group. The profile of the carbon fiber reinforced polyaryletherketone composite material made of the carbon fiber medical prepreg tape has no cytotoxic side effects, can be used in vivo, is suitable for preparing biomedical materials, and has a shear strength of 70.6-78.8MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0096] Figure 1 A diagram showing the preparation process of the carbon fiber medical prepreg provided by the present invention;
[0097] Figure 2 A schematic diagram of a three-dimensional network hydrogel structure formed on carbon fiber during the preparation of a carbon fiber medical prepreg provided by an embodiment of the present invention;
[0098] Among them, 1-carbon fiber; 2-yarn spreading roller; 3-impregnation tank A; 4-impregnation tank B; 5-constant temperature and humidity tank; 6-oven A; 7-oven B; 8-oven C; 9-high temperature pressing roller; 10-winding device. DETAILED DESCRIPTION
[0099] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0100] The experimental materials used in the embodiments and comparative examples of the present invention are as follows:
[0101] 1. Carbon fiber: Japan Toray T700SC, 12K continuous carbon fiber, single fiber diameter 6.8um;
[0102] 2. Polyaryletherketone powder: In this embodiment, polyetheretherketone (PEEK) is selected for the experiment. The PEEK is purchased from Jilin Zhongyan, 330UPF, 950 mesh, and the powder particle size is 18um;
[0103] 3. Hydroxyl terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer: purchased from BASF, brand 1: P 124, number average molecular weight Mn = ~2,200; brand 2: P 338, number average molecular weight Mn = ~14,600;
[0104] 4. Multi-arm polyethylene glycol derivatives terminated with active functional groups. The raw material of the amino-terminated multi-arm polyethylene glycol derivatives is amino-terminated four-arm polyethylene glycol: the molecular weight is 2K, i.e., 4-arm-PEG-NH2, purchased from Sigma-Aldrich;
[0105] 5. Multi-arm polyethylene glycol derivatives terminated with active functional groups. The raw material of the multi-arm polyethylene glycol derivatives terminated with thiol groups is thiol-terminated four-arm polyethylene glycol: the molecular weight is 10K, i.e. 4-arm-PEG-SH (pentaerythritol core, the core structure is pentaerythritol), purchased from Sigma-Aldrich;
[0106] 6. Vinyl sulfone terminated polyethylene glycol: VS-PEG-VS, molecular weight Mn = 3500, purchased from Sigma-Aldrich.
[0107] Preparation Example 1:
[0108] This preparation example 1 provides a vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer and a preparation method thereof, the preparation method comprising:
[0109] use P 124 (number average molecular weight Mn = ~2,200, about 5 g) was directly dissolved in 300 mL of anhydrous dichloromethane (previously dried with molecular sieves). In P 124, NaH is added under nitrogen in a molar amount of 5 times the PEG-OH groups. After hydrogen evolution, divinyl sulfone is added very quickly in a molar amount of 50 to 100 times the PEG-OH. The reaction is stirred continuously for 3 days at room temperature under a nitrogen atmosphere. The reaction solution is then neutralized with concentrated acetic acid, filtered until clear, and reduced to a minimum volume (about 10 mL) by rotary evaporation. The polymer is then dissolved in 200 mL of deionized water containing about 5 g of sodium chloride and extracted three times with 200 mL of dichloromethane. The solution is dried over sodium carbonate and the solvent is removed by rotary evaporation until the final product is obtained, after which the final product is dried under vacuum and stored under argon at -20°C. After 1 H-NMR (Bruker, model AVANCE III) was used to characterize the chemical structure. 1 H-NMR, 400 MHz, CDCl3) is: PEG-PPG-PEG capped with vinyl sulfone 1 The results confirmed by H-NMR (CDCl3) are as follows:
[0110] 6.1ppm (trans, 1H, =CH2), 6.4ppm (cis, 1H, =CH2) and 6.8ppm (1H, -SO2CH=), and the backbone structure of PEG and PPG is shown in Formula 7 (the segment structure selected in the PEG-PPG-PEG structure):
[0111]
[0112] d: (C=O)OCH2 4.3ppm; e:OCH2CH2O 3.6ppm; f: O-CH(CH3)-CH2-3.5ppm; g:
[0113] O-CH(CH3)-CH2-3.3ppm; h:O-CH(CH3)-CH2-1.1ppm.
[0114] Preparation Example 2:
[0115] This preparation example provides a vinyl sulfone terminated PEG-PPG-PEG triblock copolymer and a preparation method thereof, the preparation method comprising:
[0116] use P 338 (number average molecular weight Mn = ~14,600, about 5 g) was directly dissolved in 300 mL of anhydrous dichloromethane (previously dried with molecular sieves). In P 338, NaH is added under nitrogen in a molar amount of 5 times the PEG-OH groups. After hydrogen evolution, divinyl sulfone is added very quickly in a molar amount of 50 to 100 times the PEG-OH. The reaction is stirred continuously for 3 days at room temperature under a nitrogen atmosphere. The reaction solution is then neutralized with concentrated acetic acid, filtered until clear, and reduced to a minimum volume (about 10 mL) by rotary evaporation. The polymer is then dissolved in 200 mL of deionized water containing about 5 g of sodium chloride and extracted three times with 200 mL of dichloromethane. The solution is dried over sodium carbonate and the solvent is removed by rotary evaporation until the final product is obtained, after which the final product is dried under vacuum and stored under argon at -20°C. After 1 H-NMR (Bruker, model AVANCE III) was used to characterize the chemical structure. 1 H-NMR, 400 MHz, CDCl3) is: PEG-PPG-PEG capped with vinyl sulfone 1 The results confirmed by H-NMR (CDCl3) are as follows:
[0117] 6.1ppm (trans, 1H, =CH2), 6.4ppm (cis, 1H, =CH2) and 6.8ppm (1H, -SO2CH=), and the backbone structures of PEG and PPG are shown in Formula 8 (segment structure selected from the vinyl sulfone terminated PEG-PPG-PEG structure):
[0118]
[0119] d: (C=O)OCH2 4.3ppm; e:OCH2CH2O 3.6ppm; f: O-CH(CH3)-CH2-3.5ppm; g:
[0120] O-CH(CH3)-CH2-3.3ppm; h:O-CH(CH3)-CH2-1.1ppm.
[0121] Embodiment 1:
[0122] The present embodiment provides a method for preparing a carbon fiber medical prepreg tape, wherein the polyaryletherketone powder used in the preparation process is polyetheretherketone (PEEK), and the triblock copolymer used is a polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer terminated with vinyl sulfone; the hydrogel formed in the preparation process is a PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone and an amino-terminated multi-arm polyethylene glycol derivative generated by the Michael addition reaction of carbon-carbon double bonds and amino groups, specifically, vinyl sulfone-terminated PEG-PPG-PEG and 4-arm-PEG-NH2 form a hydrogel three-dimensional network structure.
[0123] The raw materials for preparing the carbon fiber medical prepreg tape include PEEK suspension A and PEEK suspension B; the components of the PEEK suspension A include a combination of PEEK powder and a PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone, wherein the PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone is a vinyl sulfone terminated modified P 124; The components of the PEEK suspension B include a combination of PEEK powder and an amino-terminated multi-arm polyethylene glycol derivative. The amino-terminated multi-arm polyethylene glycol derivative is 4-arm-PEG-NH2. The preparation process of the carbon fiber medical prepreg is shown in FIG. Figure 1 shown.
[0124] The preparation method comprises:
[0125] 1. Prepare PEEK suspension A;
[0126] A PEEK suspension A was prepared, wherein the main components of the suspension were: 10 g of vinyl sulfone-terminated PEG-PPG-PEG, 50 g of PEEK, and 190 g of deionized water.
[0127] The specific process is: use an ultrasonic oscillator to evenly disperse the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer in the deionized water solution, and stir until the solution is transparent and clear; weigh the PEEK resin powder in a beaker, and drop the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer mixed aqueous solution into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500 rpm; continue to stir for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of vinyl sulfone-terminated PEG-PPG-PEG to PEEK powder is 1:5. Place the prepared PEEK suspension A in a Figure 1 In the dipping tank A (3) shown.
[0128] 2. Prepare PEEK suspension B;
[0129] Prepare PEEK suspension B, wherein the main components of the suspension are: 10 g 4-arm-PEG-NH2, 50 g PEEK, and 190 g deionized water.
[0130] The specific process is: use an ultrasonic oscillator to evenly disperse 4-arm-PEG-NH2 in a deionized water solution, and stir until the solution is transparent and clear; weigh PEEK resin powder in a beaker, and drop the mixed aqueous solution of amino-terminated 4-arm-PEG-NH2 into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500rpm; continue stirring for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of 4-arm-PEG-NH2 to PEEK powder is 1:5. Place the prepared PEEK suspension B in a Figure 1 In the dipping tank B (4) shown.
[0131] 3. Fiber impregnation;
[0132] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are set as follows: yarn feeding tension 2kg, winding tension 2kg. Figure 1 As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively; the temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tanks A (3) and B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4), and the coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is as fully coated with the impregnation solution as possible to obtain the impregnated carbon fiber.
[0133] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C, and kept for 10 minutes, and the coating in the immersion tank A is completed. The specific process of coating in polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is kept at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0134] 4. Formation of three-dimensional network structure hydrogel;
[0135] After the carbon fiber (1) is immersed in the impregnation tank A (3), the carbon fiber is loaded with PEEK powder and a PEG-PPG-PEG mixture capped with vinyl sulfone. Afterwards, it enters the impregnation tank B (4), and the 4-arm-PEG-NH2 and PEEK powder in the impregnation tank B (4). The PEG-PPG-PEG mixture capped with vinyl sulfone and the 4-arm-PEG-NH2 can undergo Michael addition reaction at room temperature to obtain a hydrogel with a three-dimensional network structure. The network structure of the hydrogel can fix the PEEK powder attached to the carbon fiber on the carbon fiber. The three-dimensional network hydrogel structure formed by the vinyl sulfone-capped PEG-PPG-PEG and the 4-arm-PEG-NH2 is as shown in Figure 2 As shown;
[0136] The final gelation and fixation of PEEK powder is carried out in a constant temperature and humidity chamber (5): the pre-molded tape is introduced into the constant temperature and humidity chamber (5), the humidity of the constant temperature and humidity chamber is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity chamber (5) is adjusted to 6 hours; so that the 4-arm-PEG-NH2 and the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer fully react to form a gel structure, and the three-dimensional network structure of the hydrogel fixes the PEEK powder on the carbon fiber (1) to obtain a pre-molded prepreg tape.
[0137] 5. Drying;
[0138] The pre-shaped prepreg tapes were introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes. In oven A (6), the PEEK powder was fixed on the carbon fiber again and the water content of the hydrogel was volatilized. After the hydrogel swelled, its shape changed from large to small due to the volatilization of water content, making the PEEK powder and polyetheretherketone fit more tightly. The temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the water content of the fiber surface and the hydrogel was completely evaporated, and the PEEK powder and polyetheretherketone were more firmly attached. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to ensure that the hydrogel structure formed by the reaction of the PEG-PPG-PEG amphiphilic polymer capped with 4-arm-PEG-NH2 and vinyl sulfone collapsed and decomposed as much as possible to obtain a dry pre-shaped prepreg tape.
[0139] 6. High temperature shaping to obtain carbon fiber medical prepreg tape;
[0140] The dried predetermined prepreg tape is introduced into a high-temperature pressure roller (9) for shaping at a shaping temperature of 380° C. and a pressure of 1.5 MPa, and then cooled and introduced into a winding device (10) for winding to obtain a uniform quality carbon fiber medical prepreg tape with a PEEK mass fraction of about 30%.
[0141] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0142] A 1.2 mm thick PEEK profile was prepared by a compression molding process using a carbon fiber medical prepreg tape, wherein the profile had a length of 100 mm, a width of 100 mm, and a thickness of 1.2 mm. The molding conditions were: a pressure of 2.5 MPa, a temperature of 380° C., and a heat preservation time of 20 min; and the PEEK profile was obtained.
[0143] The PEEK profile was cultured with osteoblasts MC3T3-E1 and proved to have no cytotoxic side effects and could be used as a biomedical material.
[0144] The specific experimental process of cytotoxicity study is as follows:
[0145] Cytotoxicity was determined by live dead staining. For live dead staining, polyethylene glycol (PEG)-based substrates were washed in 70% ethanol, rinsed with phosphate buffered solution (PBS), and incubated in 8-well polystyrene (TCPs) plates. 4 Cells were treated at a density of 1 cell / mL and cultured in an incubator at 37 degrees, 5% CO2 atmosphere and 95% relative humidity for 24 hours. The viability of the cells was assessed by live-dead staining after 24 hours. In detail, cells were inoculated with 1000 μl solution containing 10 μL fluoresceindiacetate (0.5 mg / mg in acetone), 20 μL propidium iodide (0.5 mg / mL in PBS) and 970 μL PBS. Metabolically active cells can hydrolyze fluoresceindiacetate to green fluorescent fluorescein with the help of intracellular esterases. At the same time, propidium iodide can pass through the damaged cytoplasmic membrane, bind to the nucleic acid of the nucleus, and cause the nucleus to produce fluorescent red 101. After removing the dye solution and then washing with PBS, it was measured by fluorescence microscopy. For visualization of cells, fluorescein and propidium iodide were excited at 496 nm and 561 nm, respectively; and detected in the release ranges of 504 nm-559 nm and 569 nm-663 nm, respectively.
[0146] The 1.2 mm PEEK profile made of the carbon fiber medical prepreg tape was used for osteoblast culture, followed by a live / dead cell staining test, and then a fluorescence microscope was used for characterization and analysis. The live and dead cell staining (live and dead assay) results of 24 hours of in vitro MC3T3-E1 osteoblast culture showed that the cells cultured in the PEEK profile all showed green under a fluorescence microscope, indicating that the cells were alive and the sample had no cytotoxic side effects.
[0147] Embodiment 2:
[0148] This embodiment provides a method for preparing a carbon fiber medical prepreg tape, wherein the polyaryletherketone powder used in the preparation process is polyetheretherketone (PEEK), and the triblock copolymer used is a vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; the hydrogel formed in the preparation process is a vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer and a thiol-terminated multi-arm polyethylene glycol derivative generated by the Michael addition reaction of carbon-carbon double bonds and thiol groups. Specifically, the vinyl sulfone-terminated PEG-PPG-PEG and the 4-arm-PEG-SH form a hydrogel three-dimensional network structure.
[0149] The raw materials for preparing the carbon fiber medical prepreg tape include PEEK suspension A and PEEK suspension B; the components of the PEEK suspension A include a combination of PEEK powder and a PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone, wherein the PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone is a vinyl sulfone terminated modified P 124 (number average molecular weight Mn = ~2,200); the components of the PEEK suspension B include a combination of PEEK powder and a multi-arm polyethylene glycol derivative terminated with active functional groups. The multi-arm polyethylene glycol derivative terminated with thiol groups is 4-arm-PEG-SH. The preparation process of the carbon fiber medical prepreg is shown in the figure Figure 1 shown.
[0150] The preparation method comprises:
[0151] 1. Prepare PEEK suspension A;
[0152] Prepare PEEK suspension A, wherein the main components of the suspension are: 10g vinyl sulfone-terminated PEG-PPG-PEG (vinyl sulfone-terminated modified P 124, number average molecular weight Mn = ~2,200), 50g PEEK, 190g deionized water.
[0153] The specific process is: use an ultrasonic oscillator to evenly disperse the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer in the deionized water solution, and stir until the solution is transparent and clear; weigh the PEEK resin powder in a beaker, and drop the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer mixed aqueous solution into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500 rpm; continue to stir for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of vinyl sulfone-terminated PEG-PPG-PEG to PEEK powder is 1:5. Place the prepared PEEK suspension A in a Figure 1 In the dipping tank A (3) shown.
[0154] 2. Prepare PEEK suspension B;
[0155] Prepare PEEK suspension B, wherein the main components of the suspension are: 10 g 4-arm-PEG-SH, 50 g PEEK, and 190 g deionized water.
[0156] The specific process is: use an ultrasonic oscillator to evenly disperse the 4-arm-PEG-SH in the deionized water solution, and stir until the solution is transparent and clear; weigh the PEEK resin powder in a beaker, and drop the mixed aqueous solution of the amino-terminated 4-arm-PEG-SH into the beaker drop by drop. During the dropping process, control the speed of the magnetic stirrer to 500rpm; continue to stir for 60 minutes after all the solutions have been dropped, and the stirring temperature is controlled at 25°C. In this method, the mass ratio of 4-arm-PEG-SH to PEEK powder is 1:5. Place the prepared PEEK suspension B in a Figure 1 In the dipping tank B (4) shown.
[0157] 3. Fiber impregnation;
[0158] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are set as follows: yarn feeding tension 2kg, winding tension 2kg. Figure 1 As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively; the temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tanks A (3) and B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4), and the coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is as fully coated with the impregnation solution as possible to obtain the impregnated carbon fiber.
[0159] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0160] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0161] 4. Formation of three-dimensional network structure hydrogel;
[0162] After the carbon fiber (1) is immersed in the impregnation tank A (3), the carbon fiber is loaded with PEEK powder and a PEG-PPG-PEG mixture capped with vinyl sulfone. Afterwards, it enters the impregnation tank B (4), and the 4-arm-PEG-SH and PEEK powder in the impregnation tank B (4). The PEG-PPG-PEG mixture capped with vinyl sulfone and the 4-arm-PEG-SH can undergo Michael addition reaction at room temperature to obtain a hydrogel with a three-dimensional network structure. The network structure of the hydrogel can fix the PEEK powder attached to the carbon fiber on the carbon fiber. The three-dimensional network hydrogel structure formed by the vinyl sulfone-capped PEG-PPG-PEG and the 4-arm-PEG-SH is as shown in Figure 2 As shown;
[0163] The final gelation and fixation of PEEK powder is carried out in a constant temperature and humidity chamber (5): the pre-molded tape is introduced into the constant temperature and humidity chamber (5), the humidity of the constant temperature and humidity chamber is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity chamber (5) is adjusted to 6 hours; so that the 4-arm-PEG-SH and the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer fully react to form a gel structure, and the three-dimensional network structure of the hydrogel fixes the PEEK powder on the carbon fiber (1), thereby obtaining a pre-molded prepreg tape.
[0164] 5. Drying;
[0165] The pre-shaped prepreg tapes were introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes. In oven A (6), the PEEK powder was fixed on the carbon fiber again and the water content of the hydrogel was volatilized. After the hydrogel swelled, its shape changed from large to small due to the volatilization of water, so that the PEEK powder and polyetheretherketone were more closely attached. The temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the water content of the fiber surface and the hydrogel was completely evaporated, and the PEEK powder and polyetheretherketone were firmly attached. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to ensure that the hydrogel structure formed by the reaction of the PEG-PPG-PEG amphiphilic polymer capped with 4-arm-PEG-SH and vinyl sulfone collapsed and decomposed as much as possible to obtain a dry pre-shaped prepreg tape.
[0166] 6. High temperature shaping to obtain carbon fiber medical prepreg tape;
[0167] The dried predetermined prepreg tape is introduced into a high-temperature pressure roller (9) for shaping at a shaping temperature of 380° C. and a pressure of 1.5 MPa, and then cooled and introduced into a winding device (10) for winding to obtain a uniform quality carbon fiber medical prepreg tape with a PEEK mass fraction of about 30%.
[0168] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0169] A 1.2 mm thick PEEK profile was prepared by a compression molding process using a carbon fiber medical prepreg tape, wherein the profile had a length of 100 mm, a width of 100 mm, and a thickness of 1.2 mm. The molding conditions were: a pressure of 2.5 MPa, a temperature of 380° C., and a heat preservation time of 20 min; and the PEEK profile was obtained.
[0170] Referring to Example 1, a cell study on culturing the PEEK profile with osteoblast MC3T3-E1 proved that the PEEK profile has no cytotoxic side effects and can be used as a biomedical material.
[0171] Embodiment 3:
[0172] The present embodiment provides a method for preparing a carbon fiber medical prepreg tape. The polyaryletherketone powder used in the preparation process is polyetheretherketone (PEEK), and the triblock copolymer used is a vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; the hydrogel formed in the preparation process is specifically a vinyl sulfone-terminated PEG-PPG-PEG ( P338, number average molecular weight Mn = ~14,600) forms a three-dimensional network structure of hydrogel with 4-arm-PEG-NH2.
[0173] The raw materials for preparing the carbon fiber medical prepreg tape include PEEK suspension A and PEEK suspension B; the components of the PEEK suspension A include a combination of PEEK powder and a PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone, wherein the PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone is a vinyl sulfone terminated modified P 338; The components of the PEEK suspension B include a combination of PEEK powder and an amino-terminated multi-arm polyethylene glycol derivative. The amino-terminated multi-arm polyethylene glycol derivative is 4-arm-PEG-NH2. The preparation process of the carbon fiber medical prepreg is shown in FIG. Figure 1 shown.
[0174] The preparation method comprises:
[0175] 1. Prepare PEEK suspension A;
[0176] Prepare PEEK suspension A, wherein the main components of the suspension are: 10g vinyl sulfone-terminated PEG-PPG-PEG ( P 338, number average molecular weight Mn = ~14,600), 50g PEEK, 190g deionized water.
[0177] The specific process is: use an ultrasonic oscillator to evenly disperse the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer in the deionized water solution, and stir until the solution is transparent and clear; weigh the PEEK resin powder in a beaker, and drop the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer mixed aqueous solution into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500 rpm; continue to stir for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of vinyl sulfone-terminated PEG-PPG-PEG to PEEK powder is 1:5. Place the prepared PEEK suspension A in a Figure 1 In the dipping tank A (3) shown.
[0178] 2. Prepare PEEK suspension B;
[0179] Prepare PEEK suspension B, wherein the main components of the suspension are: 10 g 4-arm-PEG-NH2, 50 g PEEK, and 190 g deionized water.
[0180] The specific process is: use an ultrasonic oscillator to evenly disperse 4-arm-PEG-NH2 in a deionized water solution, and stir until the solution is transparent and clear; weigh PEEK resin powder in a beaker, and drop the mixed aqueous solution of amino-terminated 4-arm-PEG-NH2 into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500rpm; continue stirring for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of 4-arm-PEG-NH2 to PEEK powder is 1:5. Place the prepared PEEK suspension B in a Figure 1 In the dipping tank B (4) shown.
[0181] 3. Fiber impregnation;
[0182] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are set as follows: yarn feeding tension 2kg, winding tension 2kg. Figure 1As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively; the temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tanks A (3) and B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4), and the coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is as fully coated with the impregnation solution as possible to obtain the impregnated carbon fiber.
[0183] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0184] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0185] 4. Formation of three-dimensional network structure hydrogel;
[0186] After the carbon fiber (1) is immersed in the impregnation tank A (3), the carbon fiber is loaded with PEEK powder and a PEG-PPG-PEG mixture capped with vinyl sulfone. Afterwards, it enters the impregnation tank B (4), and the 4-arm-PEG-NH2 and PEEK powder in the impregnation tank B (4). The PEG-PPG-PEG mixture capped with vinyl sulfone and the 4-arm-PEG-NH2 can undergo Michael addition reaction at room temperature to obtain a hydrogel with a three-dimensional network structure. The network structure of the hydrogel can fix the PEEK powder attached to the carbon fiber on the carbon fiber. The three-dimensional network hydrogel structure formed by the vinyl sulfone-capped PEG-PPG-PEG and the 4-arm-PEG-NH2 is as shown in Figure 2 As shown;
[0187] The final gelation and fixation of PEEK powder is carried out in a constant temperature and humidity chamber (5): the pre-molded tape is introduced into the constant temperature and humidity chamber (5), the humidity of the constant temperature and humidity chamber is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity chamber (5) is adjusted to 6 hours; so that the 4-arm-PEG-NH2 and the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer fully react to form a gel structure, and the three-dimensional network structure of the hydrogel fixes the PEEK powder on the carbon fiber (1) to obtain a pre-molded prepreg tape.
[0188] 5. Drying;
[0189] The pre-shaped prepreg tapes were introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes. In oven A (6), the PEEK powder was fixed on the carbon fiber again and the water content of the hydrogel was volatilized. After the hydrogel swelled, its shape changed from large to small due to the volatilization of water content, making the PEEK powder and polyetheretherketone fit more closely. The temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the water content of the fiber surface and the hydrogel was completely evaporated, and the PEEK powder and polyetheretherketone were firmly attached. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to ensure that the hydrogel structure formed by the reaction of the PEG-PPG-PEG amphiphilic polymer capped with 4-arm-PEG-NH2 and vinyl sulfone collapsed and decomposed as much as possible to obtain a dry pre-shaped prepreg tape.
[0190] 6. High temperature shaping to obtain carbon fiber medical prepreg tape;
[0191] The dried predetermined prepreg tape is introduced into a high-temperature pressure roller (9) for shaping at a shaping temperature of 380° C. and a pressure of 1.5 MPa, and then cooled and introduced into a winding device (10) for winding to obtain a uniform quality prepreg tape with a PEEK mass fraction of about 30%.
[0192] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0193] A 1.2 mm thick PEEK profile was prepared by a compression molding process using a carbon fiber medical prepreg tape, wherein the profile had a length of 100 mm, a width of 100 mm, and a thickness of 1.2 mm. The molding conditions were: a pressure of 2.5 MPa, a temperature of 380° C., and a heat preservation time of 20 min; and the PEEK profile was obtained.
[0194] Referring to Example 1, a cell study on culturing the PEEK profile with osteoblast MC3T3-E1 proved that the PEEK profile has no cytotoxic side effects and can be used as a biomedical material.
[0195] Comparative Example 1:
[0196] This comparative example provides a method for preparing a carbon fiber medical prepreg tape, comprising:
[0197] 1. Prepare polyaryletherketone powder suspension A;
[0198] Prepare polyaryletherketone powder suspension A, wherein the main components of the suspension are: 10g PEG-PPG-PEG ( P 124), 50g PEEK, 190g deionized water solution.
[0199] The specific process is: use an ultrasonic oscillator to PEG-PPG-PEG ( P 124) amphiphilic polymer is evenly dispersed in deionized water solution and stirred until the solution is transparent and clear; PEEK resin powder is weighed in a beaker and PEG-PPG-PEG ( P 124) The mixed aqueous solution was dripped into the beaker drop by drop. During the dripping process, the speed of the magnetic stirrer was controlled at 500 rpm. After the solution was completely dripped, stirring was continued for 60 minutes, and the stirring temperature was controlled at 25°C. This method PEG-PPG-PEG ( The mass ratio of P 124) to PEEK powder is 1:5. The prepared polyaryletherketone suspension A is placed in Figure 1 The dipping tank A (3) is shown.
[0200] 2. Prepare polyaryletherketone suspension B;
[0201] A polyaryletherketone powder suspension B was prepared, wherein the main components of the suspension were: 10 g 4-arm-PEG-NH2, 50 g PEEK, and 190 g deionized water.
[0202] The specific process is: use an ultrasonic oscillator to evenly disperse 4-arm-PEG-NH2 in a deionized water solution, and stir until the solution is transparent and clear; weigh PEEK resin powder in a beaker, and drip the mixed aqueous solution of amino-terminated multi-arm polyethylene glycol derivatives into the beaker drop by drop. During the dripping process, control the speed of the magnetic stirrer to 500rpm; continue stirring for 60 minutes after all the solutions have been dripped, and the stirring temperature is controlled at 25°C. In this method, the mass ratio of 4-arm-PEG-NH2 to PEEK powder is 1:5. Place the prepared polyaryletherketone suspension B in a Figure 1 In the dipping tank B (4) shown.
[0203] 3. Fiber impregnation, attaching PEEK powder to carbon fiber;
[0204] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are preferably set as: yarn feeding tension 2kg, winding tension 2kg. Figure 1As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively. The temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tank A (3) and the impregnation tank B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4). The coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is coated with the impregnation solution as fully as possible.
[0205] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0206] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0207] 4. The hydrogel failed to form a three-dimensional network structure, and PEEK powder was further attached to the carbon fiber;
[0208] After the carbon fiber (1) is impregnated into the impregnation tank A (3), the carbon fiber is loaded with PEEK powder and PEG-PPG-PEG mixture. Afterwards, it enters the impregnation tank B (4), and the 4-arm-PEG-NH2 and PEEK powder in the impregnation tank B (4). PEG-PPG-PEG and 4-arm-PEG-NH2 without carbon-carbon double bond end groups cannot obtain a hydrogel with a three-dimensional network structure, and PEEK powder is further attached in a constant temperature and humidity tank (5): the unidirectional prepreg tape is introduced into the constant temperature and humidity tank (5), the humidity of the constant temperature and humidity tank is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity tank (5) is adjusted to 6 hours.
[0209] 5. Drying;
[0210] The unidirectional prepreg tape was introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes, and the PEEK powder was again ensured to be attached to the carbon fiber in oven A (6); the temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the moisture on the fiber surface was completely evaporated. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to ensure that the PEG-PPG-PEG amphiphilic polymer structure capped with 4-arm-PEG-NH2 and vinyl sulfone collapsed and decomposed as much as possible.
[0211] 6. High temperature setting;
[0212] The dried unidirectional prepreg tape is introduced into a high-temperature pressure roller (9) for shaping, the shaping temperature is 380° C., and the pressure is 1.5 MPa. It is then cooled and introduced into a winding device (10) for winding. After verification by thermogravimetric analysis, a uniform carbon fiber reinforced PEEK unidirectional prepreg tape with a PEEK mass fraction of about 30% is finally obtained.
[0213] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0214] A 1.2 mm thick PEEK profile was prepared by a compression molding process using a carbon fiber medical prepreg tape, wherein the profile had a length of 100 mm, a width of 100 mm, and a thickness of 1.2 mm. The molding conditions were: a pressure of 2.5 MPa, a temperature of 380° C., and a heat preservation time of 20 min; and the PEEK profile was obtained.
[0215] Comparative Example 2:
[0216] This comparative example provides a method for preparing a carbon fiber medical prepreg tape, comprising:
[0217] 1. Prepare PEEK powder suspension A;
[0218] A PEEK powder suspension A was prepared, wherein main components of the suspension were 50 g PEEK and 200 g deionized water.
[0219] The specific process is as follows: Use an ultrasonic oscillator to evenly disperse the weighed PEEK resin powder in the deionized water solution, stir until the solution is transparent and clear, control the speed of the magnetic stirrer to 500 rpm, stir for 60 minutes, and control the stirring temperature at 25°C. Place the prepared PEEK suspension A in a Figure 1 In the dipping tank A (3) shown.
[0220] 2. Prepare PEEK suspension B:
[0221] Prepare a PEEK powder suspension B, wherein the main components of the suspension are: 10 g 4-arm-PEG-NH2, 50 g PEEK, and 190 g deionized water.
[0222] The specific process is: use an ultrasonic oscillator to evenly disperse 4-arm-PEG-NH2 in a deionized water solution, and stir until the solution is transparent and clear; weigh PEEK resin powder in a beaker, and drop the mixed aqueous solution of amino-terminated multi-arm polyethylene glycol derivatives into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500rpm; continue stirring for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of 4-arm-PEG-NH2 to PEEK powder is 1:5. Place the prepared PEEK suspension B in a Figure 1 In the dipping tank B (4) shown.
[0223] 3. Fiber impregnation, attaching PEEK powder to carbon fiber;
[0224] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are preferably set as: yarn feeding tension 2kg, winding tension 2kg. Figure 1 As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively. The temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tank A (3) and the impregnation tank B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4). The coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is coated with the impregnation solution as fully as possible.
[0225] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0226] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0227] 4. Failure to form glue, further adhesion of PEEK powder on carbon fiber;
[0228] After the carbon fiber (1) is impregnated into the impregnation tank A (3), a small amount of PEEK powder is loaded on the carbon fiber. After that, it enters the impregnation tank B (4), and the 4-arm-PEG-NH2 and PEEK powder in the impregnation tank B (4) are impregnated. Without PEG-PPG-PEG and 4-arm-PEG-NH2, a hydrogel with a three-dimensional network structure cannot be obtained. The constant temperature and humidity tank (5) further attaches PEEK powder: the unidirectional prepreg tape is introduced into the constant temperature and humidity tank (5), the humidity of the constant temperature and humidity tank (5) is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity tank (5) is adjusted to 6 hours.
[0229] 5. Drying;
[0230] The unidirectional prepreg tape was introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes, and the PEEK powder was again ensured to be attached to the carbon fiber in oven A (6); the temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the moisture on the fiber surface was completely evaporated. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to ensure that the 4-arm-PEG-NH2 structure collapsed and decomposed as much as possible to obtain a dry prepreg tape.
[0231] 6. High temperature setting;
[0232] The dried prepreg tape is introduced into a high temperature pressing roller (9) for shaping, the shaping temperature is 380°C, the pressure is 1.5MPa, and then cooled, introduced into a winding device (10) for winding, and finally verified by thermogravimetric analysis, a carbon fiber reinforced PEEK unidirectional prepreg tape with a uniform mass fraction of about 95% of carbon fiber is obtained. Compared with Example 1, there is very little PEEK powder attached to the fiber. This is because the hydrogel cannot be formed, and there is no PEG-PPG-PEG non-ionic amphiphilic block copolymer. The PEEK powder in the impregnation tank A (3) is almost unable to adhere to the carbon fiber, and the PEEK powder attached to the carbon fiber falls off the fiber.
[0233] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0234] A 1.2 mm thick PEEK profile was prepared by compression molding using a carbon fiber medical prepreg tape. The profile was 100 mm long, 100 mm wide, and 1.2 mm thick. Molding conditions: pressure 2.5 MPa, temperature 380°C, insulation 20 min; the PEEK profile was obtained. The experiment found that because there were too many carbon fibers in the spline and almost no PEEK resin, qualified shaping splines could not be produced and the shear strength could not be measured.
[0235] Comparative Example 3:
[0236] This comparative example provides a method for preparing a carbon fiber medical prepreg tape, comprising:
[0237] 1. Prepare PEEK powder suspension A;
[0238] A PEEK powder suspension A was prepared, wherein main components of the suspension were 50 g PEEK and 200 g deionized water.
[0239] The specific process is as follows: PEEK resin is evenly dispersed in deionized water solution using an ultrasonic oscillator, stirred until the solution is transparent and clear, the speed of the magnetic stirrer is controlled at 500 rpm, stirred for 60 minutes, and the stirring temperature is controlled at 25°C. The prepared PEEK suspension A is placed in a Figure 1 In the dipping tank A (3) shown.
[0240] 2. Prepare PEEK suspension B;
[0241] A PEEK powder suspension B was prepared, wherein the main components of the suspension were: 50 g PEEK and 200 g deionized water.
[0242] The specific process is as follows: PEEK resin powder is evenly dispersed in deionized water solution using an ultrasonic oscillator, stirred until the solution is transparent and clear, the speed of the magnetic stirrer is controlled at 500 rpm, stirred for 60 minutes, and the stirring temperature is controlled at 25°C. The prepared PEEK suspension B is placed in Figure 1 In the dipping tank B (4) shown.
[0243] 3. Fiber impregnation, PEEK powder cannot adhere to carbon fiber;
[0244] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are preferably set as: yarn feeding tension 2kg, winding tension 2kg. Figure 1As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively. The temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tank A (3) and the impregnation tank B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4). The coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber is coated with the impregnation solution as fully as possible.
[0245] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0246] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0247] 4. Failed to form glue, and PEEK powder could not adhere to carbon fiber;
[0248] After the carbon fiber (1) is impregnated and enters the impregnation tank A (3), a small amount of PEEK powder is loaded on the carbon fiber. After that, it enters the impregnation tank B (4). Without PEG-PPG-PEG and 4-arm-PEG-NH2, a hydrogel with a three-dimensional network structure cannot be obtained. The constant temperature and humidity tank (5) further attaches PEEK powder: the unidirectional prepreg tape is introduced into the constant temperature and humidity tank (5), the humidity of the constant temperature and humidity tank (5) is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the fiber in the constant temperature and humidity tank (5) is adjusted to 6 hours.
[0249] 5. Drying;
[0250] The unidirectional prepreg tape was introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes, and the PEEK powder was again ensured to be attached to the carbon fiber in oven A (6); the temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the moisture on the surface of the carbon fiber was completely evaporated. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to obtain a dry prepreg tape.
[0251] 6. High temperature setting;
[0252] The dried prepreg tape is introduced into a high temperature pressing roller (9) for shaping, the shaping temperature is 380°C, the pressure is 1.5MPa, and then cooled and introduced into a winding device (10) for winding. The obtained carbon fiber roll contains almost no PEEK components. Thermogravimetric analysis shows that the carbon fiber mass fraction of the finally obtained carbon fiber medical prepreg tape exceeds 99%. Compared with Example 1, the fiber can hardly load PEEK, because the interface force between PEEK and carbon fiber is weak, and PEEK fails to infiltrate the carbon fiber.
[0253] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0254] A 1.2 mm thick PEEK profile was prepared by compression molding using a carbon fiber medical prepreg tape. The profile was 100 mm long, 100 mm wide, and 1.2 mm thick. Molding conditions: pressure 2.5 MPa, temperature 380°C, insulation 20 min; the PEEK profile was obtained. The experiment found that because there were too many carbon fibers in the spline and almost no PEEK resin, qualified shaping splines could not be produced and the shear strength could not be measured.
[0255] Comparative Example 4:
[0256] This embodiment provides a method for preparing a carbon fiber medical prepreg tape, wherein the polyaryletherketone powder used in the preparation process is polyetheretherketone (PEEK), and the triblock copolymer used is a vinylsulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; the hydrogel formed in the preparation process is a vinylsulfone-terminated polyethylene glycol and an amino-terminated multi-arm polyethylene glycol derivative generated by the Michael addition reaction of carbon-carbon double bonds and amino groups. The raw materials for preparing the carbon fiber medical prepreg tape include PEEK suspension A and PEEK suspension B;
[0257] The components of the PEEK suspension A include a combination of PEEK powder and vinyl sulfone-terminated PEG, wherein the vinyl sulfone-terminated PEG is a vinyl sulfone-terminated modified polyethylene glycol (VS-PEG-VS, Mn=~3400, purchased from SigmaAldrich Company);
[0258] The structure of the VS-PEG-VS is:
[0259] The components of the PEEK suspension B include a combination of PEEK powder and an amino-terminated multi-arm polyethylene glycol derivative. The amino-terminated multi-arm polyethylene glycol derivative is 4-arm-PEG-NH2. The preparation process of the carbon fiber medical prepreg is shown in FIG. Figure 1 shown.
[0260] The preparation method comprises:
[0261] 1. Prepare PEEK suspension A;
[0262] A PEEK suspension A was prepared, wherein the main components of the suspension were: 10 g of vinyl sulfone-terminated PEG, 50 g of PEEK, and 190 g of deionized water.
[0263] The specific process is: use an ultrasonic oscillator to evenly disperse the vinyl sulfone-terminated PEG polymer in a deionized water solution and stir until the solution is transparent and clear; weigh the PEEK resin powder in a beaker, and drop the vinyl sulfone-terminated PEG polymer (VS-PEG-VS) mixed aqueous solution into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500 rpm; continue stirring for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of vinyl sulfone-terminated PEG to PEEK powder is 1:5. Place the prepared PEEK suspension A in a Figure 1 In the dipping tank A (3) shown.
[0264] 2. Prepare PEEK suspension B;
[0265] Prepare PEEK suspension B, wherein the main components of the suspension are: 10 g 4-arm-PEG-NH2, 50 g PEEK, and 190 g deionized water.
[0266] The specific process is: use an ultrasonic oscillator to evenly disperse 4-arm-PEG-NH2 in a deionized water solution, and stir until the solution is transparent and clear; weigh PEEK resin powder in a beaker, and drop the mixed aqueous solution of amino-terminated 4-arm-PEG-NH2 into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500rpm; continue stirring for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of 4-arm-PEG-NH2 to PEEK powder is 1:5. Place the prepared PEEK suspension B in a Figure 1 In the dipping tank B (4) shown.
[0267] 3. Fiber impregnation;
[0268] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are set as follows: yarn feeding tension 2kg, winding tension 2kg. Figure 1 As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively; the temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tanks A (3) and B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4), and the coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is as fully coated with the impregnation solution as possible to obtain the impregnated carbon fiber.
[0269] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is spread into the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0270] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0271] 4. Formation of three-dimensional network structure hydrogel;
[0272] After the carbon fiber (1) is immersed in the impregnation tank A (3), the carbon fiber is loaded with a mixture of PEEK powder and PEG terminated with vinyl sulfone. After that, it enters the impregnation tank B (4), where the 4-arm-PEG-NH2 and PEEK powder are immersed. The PEG terminated with vinyl sulfone and the 4-arm-PEG-NH2 can undergo Michael addition reaction at room temperature to obtain a hydrogel with a three-dimensional network structure, and the network structure of the hydrogel can fix the PEEK powder attached to the carbon fiber on the carbon fiber.
[0273] The final gelation and fixation of PEEK powder is carried out in a constant temperature and humidity chamber (5): the pre-molded tape is introduced into the constant temperature and humidity chamber (5), the humidity of the constant temperature and humidity chamber is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity chamber (5) is adjusted to 6 hours; so that the 4-arm-PEG-NH2 and the PEG polymer terminated with vinyl sulfone fully react to form a gel structure, and the hydrogel with a three-dimensional network structure fixes the PEEK powder on the carbon fiber (1), thereby obtaining a pre-molded prepreg tape.
[0274] 5. Drying;
[0275] The pre-shaped prepreg tape is introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) is controlled at 70°C and the residence time is 5 minutes. In oven A (6), the PEEK powder is fixed on the carbon fiber again and the water of the hydrogel is volatilized. After the hydrogel swells, its shape changes from large to small due to the volatilization of water, so that the PEEK powder and polyetheretherketone are more closely attached. The temperature of oven B (7) is controlled at 120°C and the residence time is 20 minutes to ensure that the water on the fiber surface and the hydrogel is completely evaporated, and the PEEK powder and the polyetheretherketone are firmly attached. The temperature of oven C (8) is controlled at 260°C and the residence time is 1 hour to ensure that the hydrogel structure formed by the reaction of 4-arm-PEG-NH2 and vinyl sulfone-terminated PEG polymer and the two collapses and decomposes as much as possible to obtain a dry pre-shaped prepreg tape.
[0276] 6. High temperature shaping to obtain carbon fiber medical prepreg tape;
[0277] The dried predetermined prepreg tape is introduced into a high-temperature pressure roller (9) for shaping at a shaping temperature of 380° C. and a pressure of 1.5 MPa, and then cooled and introduced into a winding device (10) for winding to obtain a uniform quality carbon fiber medical prepreg tape with a PEEK mass fraction of about 30%.
[0278] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0279] A 1.2 mm thick PEEK profile was prepared by a compression molding process using a carbon fiber medical prepreg tape, wherein the profile had a length of 100 mm, a width of 100 mm, and a thickness of 1.2 mm. The molding conditions were: a pressure of 2.5 MPa, a temperature of 380° C., and a heat preservation time of 20 min; and the PEEK profile was obtained.
[0280] Referring to Example 1, a cell study on culturing the PEEK profile with osteoblast MC3T3-E1 proved that the PEEK profile has no cytotoxic side effects and can be used as a biomedical material.
[0281] Comparative Example 5:
[0282] This embodiment provides a method for preparing a carbon fiber medical prepreg tape. The polyaryletherketone powder used in the preparation process is polyetheretherketone (PEEK), and the triblock copolymer used is a vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; the hydrogel formed in the preparation process is a vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer and an amino-terminated multi-arm polyethylene glycol derivative generated by the Michael addition reaction of carbon-carbon double bonds and amino groups. Specifically, the vinyl sulfone-terminated PEG-PPG-PEG ( P 124, number average molecular weight Mn = ~2,200) and 4-arm-PEG-NH2 form a hydrogel three-dimensional network structure.
[0283] The raw materials for preparing the carbon fiber medical prepreg tape include PEEK suspension A and PEEK suspension B; the components of the PEEK suspension A include a combination of PEEK powder and a PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone, wherein the PEG-PPG-PEG triblock copolymer terminated with vinyl sulfone is a vinyl sulfone terminated modified P 124; The components of the PEEK suspension B include a combination of PEEK powder and an amino-terminated multi-arm polyethylene glycol derivative. The amino-terminated multi-arm polyethylene glycol derivative is 4-arm-PEG-NH2. The preparation process of the carbon fiber medical prepreg is shown in FIG. Figure 1 shown.
[0284] The preparation method comprises:
[0285] 1. Prepare PEEK suspension A;
[0286] Prepare PEEK suspension A, wherein the main components of the suspension are: 10g vinyl sulfone-terminated PEG-PPG-PEG ( P 338, number average molecular weight Mn = ~14,600), 50g PEEK, 190g deionized water.
[0287] The specific process is: use an ultrasonic oscillator to evenly disperse the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer in the deionized water solution, and stir until the solution is transparent and clear; weigh the PEEK resin powder in a beaker, and drop the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer mixed aqueous solution into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500 rpm; continue to stir for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of vinyl sulfone-terminated PEG-PPG-PEG to PEEK powder is 1:5. Place the prepared PEEK suspension A in a Figure 1 In the dipping tank A (3) shown.
[0288] 2. Prepare PEEK suspension B;
[0289] Prepare PEEK suspension B, wherein the main components of the suspension are: 10 g 4-arm-PEG-NH2, 50 g PEEK, and 190 g deionized water.
[0290] The specific process is: use an ultrasonic oscillator to evenly disperse 4-arm-PEG-NH2 in a deionized water solution, and stir until the solution is transparent and clear; weigh PEEK resin powder in a beaker, and drop the mixed aqueous solution of amino-terminated 4-arm-PEG-NH2 into the beaker drop by drop. During the addition process, control the speed of the magnetic stirrer to 500rpm; continue stirring for 60 minutes after all the solutions have been added, and control the stirring temperature at 25°C. In this method, the mass ratio of 4-arm-PEG-NH2 to PEEK powder is 1:5. Place the prepared PEEK suspension B in a Figure 1 In the dipping tank B (4) shown.
[0291] 3. Fiber impregnation;
[0292] The carbon fiber is Japan Toray T700SC, 12K continuous carbon fiber, with a single fiber diameter of 6.8um. The equipment parameters are set as follows: yarn feeding tension 2kg, winding tension 2kg. Figure 1 As shown, after the carbon fiber (1) is spread by the spread roller (2), it enters the impregnation tank A (3) and the impregnation tank B (4) respectively; the temperature of the spread process is 150°C; the spread process is performed until the thickness of the carbon fiber substrate is between 30-40μm. The carbon fiber (1) is fully impregnated in the impregnation tanks A (3) and B (4). The residence time of the carbon fiber in the impregnation tank A (3) and the impregnation tank B (4) is adjusted to 20min and 20min respectively; the number of coatings is adjusted to 5 times. The coating process is specifically as follows: the carbon fiber first enters the impregnation tank A (3), then enters the impregnation tank B (4), and then enters the impregnation tank A (3) again, and enters the impregnation tank B (4), and the coating is repeated 5 times, and the residence time in the impregnation tank A (3) and the impregnation tank B (4) is 20min and 20min respectively each time, so that the surface of the carbon fiber (1) is as fully coated with the impregnation solution as possible to obtain the impregnated carbon fiber.
[0293] The specific process of coating in polyaryletherketone suspension A is as follows: at a certain temperature of 30°C, the continuous carbon fiber is unrolled and then enters the polyaryletherketone suspension A, and the continuous carbon fiber is kept in the suspension A for a certain time of 10 minutes. Then the temperature of the polyaryletherketone suspension A system is raised to a certain temperature of 50°C and kept for 10 minutes, and the coating in the immersion tank A is completed.
[0294] The specific process of coating in the polyaryletherketone suspension B is as follows: after the continuous carbon fiber entering the immersion tank A (3) is coated, it enters the immersion tank B (4), and the temperature of the immersion tank B (4) is maintained at 30°C. At the same time, the continuous carbon fiber is kept in the suspension B for 20 minutes, and the coating in the immersion tank B is completed.
[0295] 4. Formation of three-dimensional network structure hydrogel;
[0296] After the carbon fiber (1) is immersed in the impregnation tank A (3), the carbon fiber is loaded with PEEK powder and a PEG-PPG-PEG mixture capped with vinyl sulfone. Afterwards, it enters the impregnation tank B (4), and the 4-arm-PEG-NH2 and PEEK powder in the impregnation tank B (4). The PEG-PPG-PEG mixture capped with vinyl sulfone and the 4-arm-PEG-NH2 can undergo Michael addition reaction at room temperature to obtain a hydrogel with a three-dimensional network structure. The network structure of the hydrogel can fix the PEEK powder attached to the carbon fiber on the carbon fiber. The three-dimensional network hydrogel structure formed by the vinyl sulfone-capped PEG-PPG-PEG and the 4-arm-PEG-NH2 is as shown in Figure 2 As shown;
[0297] The final gelation and fixation of PEEK powder is carried out in a constant temperature and humidity chamber (5): the pre-molded tape is introduced into the constant temperature and humidity chamber (5), the humidity of the constant temperature and humidity chamber is controlled at 45%, the temperature is controlled at 45°C, and the residence time of the carbon fiber in the constant temperature and humidity chamber (5) is adjusted to 6 hours; so that the 4-arm-PEG-NH2 and the vinyl sulfone-terminated PEG-PPG-PEG amphiphilic polymer fully react to form a gel structure, and the three-dimensional network structure of the hydrogel fixes the PEEK powder on the carbon fiber (1) to obtain a pre-molded prepreg tape.
[0298] 5. Drying;
[0299] The pre-shaped prepreg tapes were introduced into oven A (6), oven B (7) and oven C (8) respectively, wherein the temperature of oven A (6) was controlled at 70°C and the residence time was 5 minutes. In oven A (6), the PEEK powder was fixed on the carbon fiber again and the water content of the hydrogel was volatilized. After the hydrogel swelled, its shape changed from large to small due to the volatilization of water content, making the PEEK powder and polyetheretherketone fit more closely. The temperature of oven B (7) was controlled at 120°C and the residence time was 20 minutes to ensure that the water content of the fiber surface and the hydrogel was completely evaporated, and the PEEK powder and polyetheretherketone were firmly attached. The temperature of oven C (8) was controlled at 260°C and the residence time was 1 hour to ensure that the hydrogel structure formed by the reaction of the PEG-PPG-PEG amphiphilic polymer capped with 4-arm-PEG-NH2 and vinyl sulfone collapsed and decomposed as much as possible to obtain a dry pre-shaped prepreg tape.
[0300] 6. High temperature shaping to obtain carbon fiber medical prepreg tape;
[0301] The dried predetermined prepreg tape is introduced into a high-temperature pressure roller (9) for shaping at a shaping temperature of 380° C. and a pressure of 1.5 MPa, and then cooled and introduced into a winding device (10) for winding to obtain a uniform quality prepreg tape with a PEEK mass fraction of about 30%.
[0302] 7. Carbon fiber medical prepreg tape to manufacture PEEK profiles;
[0303] A 1.2 mm thick PEEK profile was prepared by a compression molding process using a carbon fiber medical prepreg tape, wherein the profile had a length of 100 mm, a width of 100 mm, and a thickness of 1.2 mm. The molding conditions were: a pressure of 2.5 MPa, a temperature of 380° C., and a heat preservation time of 20 min; and the PEEK profile was obtained.
[0304] Referring to Example 1, a cell study on culturing the PEEK profile with osteoblast MC3T3-E1 proved that the PEEK profile has no cytotoxic side effects and can be used as a biomedical material.
[0305] Comparative Example 6:
[0306] Comparative Example 6 uses an acrylate-terminated PEG-PPG-PEG triblock copolymer to replace the vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer, and the other preparation processes are consistent with Example 1. The preparation method of the acrylate-terminated PEG-PPG-PEG triblock copolymer can refer to the Chinese patent (grant number ZL202410182240.1), as follows:
[0307] The OH-terminated P 124 and potassium carbonate were dried in a vacuum oven at 110°C for 4 hours to remove moisture. Then, under nitrogen protection, a 50 mL three-necked flask was added P 124 (number average molecular weight Mn = ~2,200, 5 g) and potassium carbonate (3 g) were mixed in dichloromethane solvent. Acryloyl chloride (1 mL) was added dropwise in an ice-water bath. The mixture was stirred at 60°C for 4 days under nitrogen protection. The solution was filtered and then poured into ice-cold petroleum ether (cooled by ice water). The solution was stirred for 10 minutes and then the crude product was isolated. The crude product was dissolved in 50 mL of dichloromethane, and then extracted three times with a saturated NaCl solution. The organic layer was collected and dried over magnesium sulfate overnight. The magnesium sulfate was then removed by filtration, and the solvent was subsequently removed by reduced pressure distillation to obtain an acrylate-terminated PEG-PPG-PEG triblock copolymer. The chemical structure was characterized by 1H-NMR nuclear magnetic resonance (Bruker, model AVANCE III), and its nuclear magnetic spectrum (1H-NMR, 400 MHz, CDCl3) was: The acrylate-terminated PEG-PPG-PEG was confirmed by 1H NMR (CDCl3). The structure of the acrylate-terminated PEG-PPG-PEG triblock copolymer is as follows (wherein, x is 1-100, y is 1-100, and z is 1-100):
[0308]
[0309] Test of interlaminar shear performance (shear strength): The interlaminar shear performance of the PEEK profiles prepared by the continuous carbon fiber reinforced prepreg tapes prepared by the methods of Examples 1 to 3 and Comparative Examples 1 to 6 was tested on a Shimadzu AGS-X universal testing machine. The test specimens for shear strength testing were prepared according to GB / T3355-2005 "Test Method for Longitudinal and Transverse Shear of Fiber Reinforced Plastics". The specimen loading speed was 2 mm / min, and 5 samples were tested in each group, and the results were averaged. Wetting condition test: The sample was quickly broken along the fiber direction at room temperature, and the adhesion between the carbon fiber and the resin at the cross section was observed. Among them, more loose carbon fibers were observed, which was considered poor; a small amount of loose carbon fibers were observed, which was considered good; no loose carbon fibers were observed, which was considered excellent.
[0310] The test results of Example 1 show that the carbon fiber impregnation is excellent. The test results are shown in Table 1:
[0311] Table 1
[0312]
[0313] From the data in Table 1, it can be seen that the shear strengths of Example 1, Example 2 and Example 3 are between 70.0 and 80.0 MPa. All three examples adopt a gel structure formed by a thermosensitive triblock copolymer of PEG-PPG-PEG terminated with vinyl sulfone to attach and fix the poly(aryletherketone) powder on the carbon fiber, and then obtain the result by hot pressing. The specific process of attaching and fixing the poly(aryletherketone) powder on the carbon fiber by the gel structure is as follows: first, the temperature of the solution system containing the thermosensitive triblock copolymer is increased so that the triblock copolymer forms a gel, thereby causing the poly(aryletherketone) powder to attach to the carbon fiber; and then the triblock copolymer and the multi-arm polyethylene glycol derivative terminated with active functional groups undergo a Michael addition reaction to generate a three-dimensional network structure hydrogel, thereby further fixing the poly(aryletherketone) powder on the carbon fiber. The hydrogel structure is a three-dimensional network structure of a hydrogel generated by vinyl sulfone-terminated PEG-PPG-PEG and a multi-arm polyethylene glycol derivative containing an active functional group amino or thiol-terminated, which further fixes the PEEK powder on the carbon fiber. The advantages of the embodiments 1, 2 and 3 are that the PEG-PPG-PEG triblock copolymer is used as a non-ionic surfactant, and its hydrophilic and hydrophobic chain segment structure can be used as a "bridge" to connect the carbon fiber and the PEEK interface, so that the wettability of the carbon fiber and the PEEK resin is enhanced, and the PEEK resin is more evenly attached to the carbon fiber; at the same time, the temperature-sensitive property of the copolymer is utilized, and the temperature of the solution system containing the temperature-sensitive triblock copolymer is increased, so that the triblock copolymer forms a gel, thereby causing the polyaryletherketone powder to adhere to the carbon fiber. Afterwards, the PEEK powder attached to the carbon fiber was further fixed on the carbon fiber using a three-dimensional network structure hydrogel formed by vinyl sulfone-capped PEG-PPG-PEG and a multi-arm polyethylene glycol derivative capped with an active functional group, thereby increasing the content of PEEK resin in the carbon fiber. The shear strength of the PEEK profiles prepared by the three prepreg tapes reached above 70.0 MPa.
[0314] Compared with Comparative Example 4, Example 1 replaces the vinyl sulfone-terminated PEG-PPG-PEG in the impregnation tank A of Example 1 with the vinyl sulfone-terminated PEG of Comparative Example 4. This makes the PEG in Comparative Example 4 not have the function of the amphiphilic nonionic surfactant of the PEG-PPG-PEG triblock copolymer, and it cannot serve as a good "bridge" connecting the carbon fiber and the PEEK interface. The carbon fiber has poor wettability with the PEEK resin, which makes it difficult for the PEEK powder to adhere to the carbon fiber. It can only adhere and fix a certain amount of PEEK powder by forming a hydrogel through the vinyl sulfone-terminated PEG and 4-arm-PEG-NH2, resulting in a shear strength of only 31.7 MPa.
[0315] Compared with Comparative Example 1, the vinyl sulfone-terminated PEG-PPG-PEG in the impregnation tank A of Example 1 is replaced by PEG-PPG-PEG of Comparative Example 1, so that Comparative Example 1 cannot form a hydrogel to further fix the PEEK powder attached to the carbon fiber, resulting in the PEEK powder not being well evenly dispersed and tightly fixed in the carbon fiber through the three-dimensional network structure, so that the shear strength is 40.3 MPa.
[0316] Comparative Examples 2 and 3 have neither amphiphilic surfactants nor hydrogels, which results in that it is difficult for PEEK powder to adhere to the carbon fiber and it is difficult to further fix the adhered PEEK powder to the carbon fiber, so that the PEEK content (mass fraction) in the carbon fiber / PEEK prepreg tape does not exceed 5% at most. The carbon fiber / PEEK prepreg tape produced in this way is difficult to be molded into a profile of a certain size (such as the 1.2 mm thickness described in the article) because there is too little PEEK powder resin matrix, resulting in a profile with a thickness of 1.2 mm cannot be shaped.
[0317] Compared with Example 5, in Example 1, the coating residence temperature of vinyl sulfone-terminated PEG-PPG-PEG in immersion tank A is increased from 30°C to 50°C, and the thermosensitive effect of vinyl sulfone-terminated PEG-PPG-PEG is utilized to form gel; while the coating residence temperature of vinyl sulfone-terminated PEG-PPG-PEG in immersion tank A in Comparative Example 5 is maintained at 30°C, and the thermosensitive effect of vinyl sulfone-terminated PEG-PPG-PEG is not utilized to form gel; resulting in less PEEK powder attached in each step, making it difficult for PEEK powder to attach to the continuous carbon fiber filaments, and only through the formation of hydrogel by vinyl sulfone-terminated PEG-PPG-PEG and 4-arm-PEG-NH2 to attach and fix a certain amount of PEEK powder, resulting in a low shear strength of only 50.1 MPa.
[0318] The only difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses acrylate-terminated PEG-PPG-PEG triblock copolymer to replace the vinyl sulfone-terminated PEG-PPG-PEG triblock copolymer, and the other preparation processes are exactly the same as Example 1. It is found that the shear strength of Comparative Example 6 is only 42.5MPa, and the shear strength performance of Example 1 is 78.8MPa, which is 85.4% higher than that of Comparative Example 6. It can be seen that the advantages of vinyl sulfone-terminated PEG-PPG-PEG over acrylate-terminated PEG-PPG-PEG in the present invention are extremely obvious. There are two main advantages: First, in terms of using the temperature sensitivity of the material to attach polyaryletherketone to continuous carbon fiber threads, experiments have found that the gel formed by acrylate-terminated PEG-PPG-PEG at elevated temperatures easily causes the attached polyaryletherketone powder to fall off and not adhere firmly. This is because the ester bond structure of the acrylate in acrylate-terminated PEG-PPG-PEG is easily hydrolyzed, which causes the temperature sensitivity of acrylate-terminated PEG-PPG-PEG to be unable to be well utilized in attaching polyaryletherketone powder, resulting in failure to produce normally. The vinyl sulfone structure of vinyl sulfone-terminated PEG-PPG-PEG is particularly stable, and the chemical bond is strong and not easy to break. When the temperature is raised, the vinyl sulfone-terminated PEG-PPG-PEG undergoes a liquid-solid phase transition from solution to gel, and the adhesion is strong and stable. The gel formed by the solution system containing the thermosensitive triblock copolymer can firmly attach the continuous carbon fiber thread to polyaryletherketone. Second, in terms of further fixing polyaryletherketone in the three-dimensional network structure hydrogel, acrylate-terminated PEG-PPG-PEG not only causes the polyaryletherketone attached to the continuous carbon fiber thread to have weak adhesion, but also easily falls off, resulting in the inability to produce normally. This is also because the adhesion of the hydrogel formed by acrylate-terminated PEG-PPG-PEG is far less strong than that of vinyl sulfone-terminated, and the ester bonds contained in acrylate-terminated PEG-PPG-PEG are particularly easy to degrade. The three-dimensional network structure of the hydrogel is not easy to maintain for a long time. The degradation of the hydrogel formed by acrylate-terminated PEG-PPG-PEG will cause the polyaryletherketone fixed on the continuous carbon fiber thread to fall off, resulting in the inability to stably produce the product.
[0319] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a carbon fiber medical prepreg tape and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a carbon fiber medical prepreg tape, characterized in that: The preparation method of the carbon fiber medical prepreg tape comprises: coating continuous carbon fiber in polyaryletherketone suspension A and polyaryletherketone suspension B; then preforming, drying and shaping to obtain the carbon fiber medical prepreg tape; The components of the polyaryletherketone suspension A include polyaryletherketone powder and a triblock copolymer; the components of the polyaryletherketone suspension B include polyaryletherketone powder and a multi-arm polyethylene glycol derivative terminated with active functional groups; The triblock copolymer has a critical temperature, below which the aqueous solution of the triblock copolymer is in a mixed solution state; above which the aqueous solution of the triblock copolymer forms a gel state; The specific process of coating the polyaryletherketone suspension A is as follows: at temperature a, immersing the continuous carbon fiber in the polyaryletherketone suspension A, and maintaining the continuous carbon fiber in the suspension A for a residence time t1; then raising the temperature of the polyaryletherketone suspension A to temperature b, and maintaining the continuous carbon fiber in the suspension B for a residence time t2; the value of the temperature a is less than the temperature value of the critical temperature, and the value of the temperature b is greater than the temperature value of the critical temperature. This process enables the triblock copolymer to form a gel on the continuous carbon fiber, thereby causing the polyaryletherketone powder to adhere to the continuous carbon fiber; The triblock copolymer is a polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer terminated with vinyl sulfone; The specific process of coating in the polyaryletherketone suspension B is as follows: immersing the continuous carbon fiber coated in the polyaryletherketone suspension A into the polyaryletherketone suspension B; during the immersion in the polyaryletherketone suspension B, the triblock copolymer attached to the continuous carbon fiber undergoes a Michael addition reaction with the multi-arm polyethylene glycol derivative terminated with active functional groups to generate a three-dimensional network structure hydrogel, and the polyaryletherketone powder is further fixed on the continuous carbon fiber.
2. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The polyaryletherketone powders in the polyaryletherketone suspension A and the polyaryletherketone suspension B independently include any one of polyetheretherketone, polyetherketoneketone, polyetherketone, polyetheretherketoneketone or polyetherketoneetherketoneketone, or a combination of at least two thereof.
3. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The vinyl sulfone terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer has a structure as shown in Formula 1: Where x is 1-100, y is 1-100, and z is 1-100.
4. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The preparation method of the vinyl sulfone terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer comprises: reacting a hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer, sodium hydride and divinyl sulfone to obtain the vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer; The hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer has a structure as shown in Formula 2: Where x is 1-100, y is 1-100, and z is 1-100; The hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer is mixed with sodium hydride in an anhydrous and oxygen-free solvent under nitrogen protection, and then divinyl sulfone is added to react; The molar ratio of the hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to sodium hydride is (0.1-100): 1; The molar ratio of the hydroxyl-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to divinyl sulfone is (0.1-200):
1.
5. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The multi-arm polyethylene glycol derivatives terminated with active functional groups include amino-terminated multi-arm polyethylene glycol derivatives and / or thiol-terminated multi-arm polyethylene glycol derivatives; The multi-arm polyethylene glycol derivative terminated with active functional groups includes any one of amino-terminated three-arm polyethylene glycol derivatives, amino-terminated four-arm polyethylene glycol derivatives, amino-terminated six-arm polyethylene glycol derivatives, amino-terminated eight-arm polyethylene glycol derivatives, thiol-terminated three-arm polyethylene glycol derivatives, thiol-terminated four-arm polyethylene glycol derivatives, thiol-terminated six-arm polyethylene glycol derivatives or thiol-terminated eight-arm polyethylene glycol derivatives, or a combination of at least two thereof.
6. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The preparation method of the polyaryletherketone suspension A comprises: Mixing polyaryletherketone powder, a vinyl sulfone-terminated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and water, and performing a first stirring to obtain the polyaryletherketone suspension A; Preferably, the mass ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer terminated with vinyl sulfone in the polyaryletherketone suspension A to the polyaryletherketone powder is (0.1-10):1; the mass ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer terminated with vinyl sulfone in the polyaryletherketone suspension A to the polyaryletherketone suspension A is (0.01-0.5):1; The preparation method of the polyaryletherketone suspension B comprises: Mixing polyaryletherketone powder, multi-arm polyethylene glycol derivative terminated with active functional groups and water, and stirring for a second time to obtain the polyaryletherketone suspension B; The mass ratio of the multi-arm polyethylene glycol derivative terminated with active functional groups to the polyaryletherketone powder in the polyaryletherketone suspension B is (0.1-10):
1.
7. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The multi-arm polyethylene glycol derivative terminated with active functional groups includes a structure as shown in any one of Formulas 3-6: Where n is 1-100; The number average molecular weight of the multi-arm polyethylene glycol derivative terminated with active functional groups is 200-50000.
8. The preparation method according to claim 1, characterized in that: The temperature a is 10-40°C; The temperature b is 30-75°C; The residence time t1 is 10-18000s; The residence time t2 is 10-18000s; The critical temperature is 30-60°C.
9. The method for preparing the carbon fiber medical prepreg tape according to claim 1, characterized in that: The drying process is to introduce the prepreg tape after preforming into oven A, oven B and oven C in sequence; The temperature of the oven A is 25-105°C; The residence time of the prepreg tape in oven A is 10-18000s; The temperature of the oven B is 25-180°C; The residence time of the prepreg tape in oven B is 10-18000s; The temperature of the oven C is 25-350°C; The residence time of the prepreg tape in the oven C is 10-36000s; The step of cooling after shaping is also included; The setting temperature is 300-450°C; The shaping pressure is 0.5-10MPa; The shaping time is 10-18000s.
10. Application of the carbon fiber medical prepreg prepared by the preparation method according to any one of claims 1 to 9 in medical devices; The applications include 3D printing of medical materials, artificial prostheses, medical catheters, oral implants, maxillofacial bones, heart valves, infusion ports, pacemaker housings, medical aiming rods, medical aiming frames, human bone locking systems, medical wrenches, medical connectors, medical positioning frames, surgical head frames and retractor systems, medical handles, medical puncture needles, medical connectors, medical sutures, artificial bones, artificial joints, femoral condyles, bone nails, screws, anchors, rivets, intramedullary nails, bone plates, tibial trays, skull repair systems or spinal intervertebral fusion devices.
Citation Information
Patent Citations
Preparation method of high-performance carbon fiber reinforced PEEK prepreg and PEEK-based board
CN116751381A
A carbon fiber reinforced polyaryletherketone medical composite material and its preparation method and application
CN117736566B